2016
DOI: 10.1017/thg.2015.97
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake at 9 Years and Subsequent Body Mass Index in Adolescent Boys and Girls: A Study of Monozygotic Twin Pairs

Abstract: There is a lack of evidence pointing to specific dietary elements related to weight gain and obesity prevention in childhood and adulthood. Dietary intake and obesity are both inherited and culturally transmitted, but most prospective studies on the association between diet and weight status do not take genetics into consideration. The objective of this study was to document the association between dietary intake at 9 years and subsequent Body Mass Index (BMI) in adolescent monozygotic boy and girl twin pairs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Differing associations by sex were also noted in a prospective study of genetically identical twin pairs with shared environments ( 48 ). Variation in dietary intake at age 9 y between sets of twins was compared with subsequent differences in BMI at age 14 y.…”
Section: Resultsmentioning
confidence: 89%
“…Differing associations by sex were also noted in a prospective study of genetically identical twin pairs with shared environments ( 48 ). Variation in dietary intake at age 9 y between sets of twins was compared with subsequent differences in BMI at age 14 y.…”
Section: Resultsmentioning
confidence: 89%
“…Research indicates beverage type, such as sugar‐sweetened beverages (SSBs), is associated with child weight status; but when it comes to milk, results are mixed. Some studies demonstrate low consumption of milk in childhood is a risk factor for obesity, while others indicate the opposite . A recent comprehensive review found no evidence that milk consumption contributes to obesity risk among adolescents; however, the authors note less evidence to support this conclusion among children less than 8 years of age .…”
Section: Introductionmentioning
confidence: 97%
“…Some studies demonstrate low consumption of milk in childhood is a risk factor for obesity, [9][10][11][12] while others indicate the opposite. 13,14 A recent comprehensive review found no evidence that milk consumption contributes to obesity risk among adolescents; however, the authors note less evidence to support this conclusion among children less than 8 years of age. 15 A study of the association of dairy and adiposity in China, one of the few non-Western nations represented in this literature, similarly found no association between dairy consumption and weight status among adolescents.…”
mentioning
confidence: 98%
“…Unexpectedly, obesity frequency was significantly higher in the group consuming three or more fruits per day compared to the group consuming less than three fruits per day. In a study of monozygotic twin pairs, lower consumption of fruit showed an association with higher BMIs [21]. In a longitudinal study, relative risk of becoming or remaining overweight/obese compared to the normal weight status increased when fruit and vegetable consumption increased [7].…”
Section: Discussionmentioning
confidence: 94%